2021
DOI: 10.3389/fped.2021.729329
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment Without Any Intervention Compared With Other Therapeutic Strategies for Symptomatic Patent Ductus Arteriosus in Extremely Preterm Infants: A Nationwide Cohort Study in Korea

Abstract: Objective: Although symptomatic treatment is the most preferred treatment strategy for proven symptomatic patent ductus arteriosus (PDA), a considerable number of infants only received conservative treatment without any pharmacological or surgical interventions in the lower gestational age and lower birth weight group in Korea. We compared in-hospital outcomes of infants treated conservatively without any intervention and those of infants managed by other therapeutic strategies in extremely preterm infants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…This result remained significant following sensitivity analyses and subgroup analyses based on sex and GA. This finding is consistent with data from the Korean national cohort, 6 the EPIPAGE 2 national population-based cohort from France, 4 and the comparative study between Japan and Canada. 3 Pathophysiologically, the consequences of left-to-right shunting through the ductus arteriosus include pulmonary edema, congestive heart failure and reduced systemic blood flow leading to peripheral organ ischemia, which may compromise the survival for extremely preterm infants, and previous studies have shown that persistent PDA was associated with increased mortality in premature infants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result remained significant following sensitivity analyses and subgroup analyses based on sex and GA. This finding is consistent with data from the Korean national cohort, 6 the EPIPAGE 2 national population-based cohort from France, 4 and the comparative study between Japan and Canada. 3 Pathophysiologically, the consequences of left-to-right shunting through the ductus arteriosus include pulmonary edema, congestive heart failure and reduced systemic blood flow leading to peripheral organ ischemia, which may compromise the survival for extremely preterm infants, and previous studies have shown that persistent PDA was associated with increased mortality in premature infants.…”
Section: Discussionsupporting
confidence: 90%
“… 1 , 2 Clinically, medical treatment has been widely used to close the ductus arteriosus, with data from several large national and international cohort studies showing that a large proportion (21–51%) of very low birth weight infants were medically treated for PDA. 3 , 4 , 5 , 6 , 7 , 8 However, several randomised clinical trials 9 , 10 , 11 , 12 and observational cohort studies 13 , 14 , 15 , 16 in recent years have shown that PDA treatment did not improve outcomes, prompting calls not to treat PDA in preterm infants actively. Nevertheless, these studies included relatively small proportions and absolute numbers of extremely preterm infants 10 , 13 , 14 , 15 , 16 who are the most vulnerable population to the harm of PDA, homogenised infants with different severity of disease, 12 , 13 , 14 , 15 , 16 focused mainly on composite outcomes, 10 , 12 , 13 , 15 and authorised rescue therapy in the non-treatment group.…”
Section: Introductionmentioning
confidence: 99%
“…Color Doppler ultrasonography screening was routinely performed in all preterm infants who required respiratory support on the third day of life. Hemodynamically significant PDA (hsPDA) was diagnosed when a DA was present with predominantly left-to-right shunting across the DA associated with (1) left-atrium-to-aorta ratio (LA./Ao ratio) ≥ 1.5 and (2) PDA diameter (measured at its narrowest part, the end of pulmonary arterial) ≥ 1.5 mm, and when there were two out of the following clinical symptoms caused by PDA: (1) systolic or continuous murmur; (2) precordial pulsation distress; (3) hypotension; (4) respiratory distress; and (5) pulmonary edema or cardiomegaly (cardiothoracic ratio > 60%) on chest X-ray ( 23 , 24 ). Echocardiograms were performed by an experienced pediatric sonographer using a Mindray M9 ultrasound scanner (Mindray, China) with a 10-MHz probe.…”
Section: Methodsmentioning
confidence: 99%
“…(3) hypotension; (4) respiratory distress; and (5) pulmonary edema or cardiomegaly (cardiothoracic ratio > 60%) on chest X-ray (23,24). Echocardiograms were performed by an experienced pediatric sonographer using a Mindray M9 ultrasound scanner (Mindray, China) with a 10-MHz probe.…”
Section: Echocardiography Diagnosis and Treatmentmentioning
confidence: 99%
“…As a result, divergent perspectives persist, with one faction asserting that PDA treatment plays a role in preventing adverse neonatal outcomes, while another contends that it does not offer such preventive benefits [ 9 , 10 ]. A conservative approach to managing PDA, encompassing strategies such as fluid restriction, diuretics, and higher positive airway end-expiratory pressure, has gained increasing favor [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%